Service public local des déchets ménagers. A la recherche d'indicateurs de performance. - Gérard Bertolini (Développement Durable et Territoires)
As other public services, the municipal waste service needs to evaluate its performances and is accountable for its results. This evaluation requires the definition of criteria and the selection of indicators in order to measure the  progress and to allow comparisons with other municipal waste services too. Because the performance has many facets, a multi-criteria approach will be used. In the light of an analysis of feasibility and relevance, the paper puts forwards few, quite simple and complementary indicators which are gathered up into a synoptic table and make up an instrument panel.